Blockade of the Brachial Plexus Abolishes Activation of Specific Brain Regions by Electroacupuncture at Li4: A Functional Mri Study. Issue 6 (December 2015) - Gu, Weidong; Jiang, Wei; He, Jingwei; Liu, Songbin; Wang, Zhaoxin
Objective: Our aim was to test the hypothesis that electroacupuncture (EA) at acupuncture point LI4 activates specific brain regions by nerve stimulation that is mediatied through a pathway involving the brachial plexus. Methods: Twelve acupuncture naive right-handed volunteers were allocated to receive three sessions of EA at LI4 in a random different order (crossover): (1) EA alone (EA); EA after injection of local anaesthetics into the deltoid muscle (EA+LA); and (3) EA after blockade of the brachial plexus (EA+NB). During each session, participants were imaged in a 3 T MRI scanner. Brain regions showing change in blood oxygen level-dependent (BOLD) signal (activation) were identified. Subjective acupuncture sensation was quantified after functional MRI scanning was completed. Results were compared between the three sessions for each individual, and averaged. Results: Blockade of the brachial plexus inhibited acupuncture sensation during EA. EA and EA+LA activated the bilateral thalamus, basal ganglia, cerebellum and left putamen, whilst no significant activation was observed during EA+NB. The BOLD signal of the thalamus correlated significantly with acupuncture sensation score during EA. Conclusions: Blockade of the brachial plexus completely abolishes patterns of brain activation induced by EA at LI4. The results suggest that EA activates specific brain regions through stimulation of the local nerves supplying the tissues at LI4, which transmit sensory information via the brachial plexus. Trial Registration Number: ChiCTR-OO-13003389.